Analysis of Samsung's internationalization process and the strategies implemented to generate an effective positioning of its brand and products in foreign markets. - Musaed Almutairi; Shivam Mehta; Fatima Al Rashidi; María Alejandra Villa; Felicia Anggawinata (AIBPM Publisher, 2019)
Samsung is a leading technology company worldwide. Its activities focus on innovative product designs that contribute to people's lives and generate substantial progress in them, through social prosperity. It is also a company established since its inception in the idea of combining creativity, partnership and great people to strategically address their work. Likewise, it wants its brand to be loved around the world, to be an innovative company and to be admired. For this reason, it promotes the value shared with its partners and collaborators, as well as with its own employees. Nowadays, Samsung is a company that is found in most countries and, therefore, despite not having a business center in all countries, its products are in every corner of the world. However, even though it is currently a multinational company and a leader in the technology sector; This company started like any other, as a business idea and progressing in small steps. In this way, the present work aims to identify and analyze all these small but significant steps that allowed Samsung to become the company that it is today and the way in which it has been possible to reach so many countries. In other words, the purpose of this paper is oriented towards the study of the internationalization processes carried out by the company to reach the different countries. In this way, variables such as: industry and competition analysis, company’s challenges, entry mode to different countries, promotional channels, prices, logistics, finance, human resources and product design will be included. Likewise, the way in which the company has managed the competition with other large technology companies in the world and what barriers it has overcome to get ahead of these will be investigated.